Animal health and welfare in organic agriculture (CABI, 2004)
This book was conceived as an activity of the Network on Animal Health and Welfare in Organic Agriculture, an EU funded network of researchers from 13 countries, and most of the authors were drawn from the network. A problem identified by the authors is the diversity that occurs inevitablyin organic agriculture, as it must adapt to the local conditions. Because of this they have limited the scope of the book to organic farming in Europe. The 17 chapters cover: the principles and values of organic farming; a historical perspective of animals in agriculture; diversity in organic livestock systems; organic livestock standards; welfare and ethics; understanding animal behaviour in organic systems; applied ethology in improving welfare; mutilations (including dehorning, debeaking); assessing animal welfare; humans in managing organic herds; health and disease on organic farms; promoting health and welfare through planning; treatment of animals; grassland management and parasite control; feeding; breeding; and future challenges. In the appendix the objectives of the Network of Animal Health and Welfare in Organic Agriculture are listed with its main conclusions and recommendations on the development of standards and regulations, development of systems and training, and research needs.